A atuação dos profissionais de psicologia da Vara da Infância e Juventude na política de adoção - Albuquerque, Leonam Amitaf Ferreira Pinto de (2019)
The general objective is to analyze the performance of the Psychology professionals of the Court of Childhood and Youth in the policy of adoption. The specific objectives are: to identify the actions attributed to these professionals by the norms of the policy of adoption; to map their biological, social and demographic characteristics; to characterize their academic formation; to understand their conceptions of social policy; and to analyze the meanings attributed by them to their action in the policy of adoption. It adopts as theoretical reference the Critical Perspective and Historical-Cultural Psychology, using the categories social policy and meaning. The field work was done through documentary analysis of normative of the adoption policy, semi-structured interview with professionals of Psychology of public institutions linked to the Justice of the Childhood and Youth and questionnaire of biological, social and demographic information. The data of the documentary analysis and the interview were analyzed by the Content Thematic Analysis and the information of the questionnaire was submitted to the descriptive analysis. The results indicated the actions attributed by the norms of the adoption policy require practices of technical and individual character. The biological, social and demographic characteristics of the participants reveal a predominance of women, who declare themselves to be brown. The academic formation, despite being considered scarce and restricted, being complemented by the work experience, contributes to the performance. The social policy conceptions refer to the role of the State and the government action in the implementation of public policies. The meanings attributed to the action in the policy of adoption relate to objective and palpable elements, pertinent to the function of legal analyst.